Economists, incentives, judgment, and the European CVAR approach to macroeconometrics - David C. Colander (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
This paper argues that the DSGE approach to macroeconometrics is the dominant approach because it meets the institutional needs of the replicator dynamics of the profession, not because it is necessarily the best way to do macroeconometrics. It further argues that this 'DSGE theory-first' approach is inconsistent with the historical approach that economists have advocated in the past and that the alternative European CVAR approach is much more consistent with economist's historically used methodology, correctly understood. However, because the European CVAR approach requires explicit researcher judgment, it does not do well in the replicator dynamics of the profession. The paper concludes with the suggestion that there should be an increase in dialog between the two approaches.
Keywords: B4; 330; Methodology; macroeconometrics; general to specific; DSGE; VAR; judgment; incentives; Makroökonomik; Dynamisches Gleichgewicht; VAR-Modell; Wissenschaftliche Methode; Vergleich; Publikationsanalyse